2012
DOI: 10.1177/0265407511431183
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and marital satisfaction within enduring relationships

Abstract: In this study of 125 heterosexual long-wed couples, we examined both spouses' personality traits and relative differences in partner perceptions of personality as predictors of marital satisfaction, simultaneously for both husbands and wives. As hypothesized, each of the Big Five personality traits emerged as significantly associated with marital satisfaction though significant between-trait and between-sex differences were observed. Most notably, trait levels predicted marital satisfaction less consistently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 51 publications
7
72
1
3
Order By: Relevance
“…Neuroticism proved to be especially problematic for quality of relationships. Claxton et al (2012) pointed out the reasons for the differences in research results concerning the role of different personality traits in marital quality explanation. One of them is the change over the course of marriage, meaning that in different periods of married life different traits could play a significant role.…”
Section: Marital Quality and Personality Traitsmentioning
confidence: 99%
“…Neuroticism proved to be especially problematic for quality of relationships. Claxton et al (2012) pointed out the reasons for the differences in research results concerning the role of different personality traits in marital quality explanation. One of them is the change over the course of marriage, meaning that in different periods of married life different traits could play a significant role.…”
Section: Marital Quality and Personality Traitsmentioning
confidence: 99%
“…More research on the relationships between assets and marital satisfaction is needed. First, many studies have confirmed gender differences in marital satisfaction (Claxton, O'Rourke, Smith, & DeLongis, 2012). Asset effects on marital satisfaction may also have different patterns between wives and husbands.…”
mentioning
confidence: 98%
“…And are these considerations more important for the lower educated, and does the importance differ by country? Some studies also have suggested that the combination of personality traits within the couple matters (Claxton et al, 2012;Rammstedt et al, 2012) for union stability, which is a possibility left unexamined by this paper.…”
Section: Discussionmentioning
confidence: 73%
“…They found effects of neuroticism and conscientiousness on marital satisfaction (Claxton et al, 2012;Robins et al, 2000), and some also found effects for extraversion and agreeableness (Noftle & Shaver, 2006;White et al, 2004). In addition, other constructs such as negative emotionality and child-mother attachment styles seem related to marital satisfaction too (Robins et al 2000;Shaver & Brennan, 1992) All in all the effects of personality on marital stability and its distribution across society remain unclear and will therefore be investigated in this paper.…”
Section: Education and Divorcementioning
confidence: 96%